(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
As Maria Teresa Grassi already highlighted, decorated coarse ware represents an underestimated and yet a key aspect for deciphering the complexity of cultural interactions in central Cisalpine regions (i.e., eastern Piedmont, Lombardy, Emilia, and western Veneto). The period addressed is the second half of the 1st millennium BC to the early imperial age when the Po valley is a mosaic of cultures and social actors on the move, and whose material culture challenges traditional interpretative categories. The aim of this paper is to discuss some technical and theoretical issues related to a specific class of coarse ware. This pottery, handmade or manufactured on the slow potter’s wheel, is decorated with styles and techniques influenced by non-local neighbouring cultures (e.g., Liguria, Central Europe), showing a super-regional and hybridized cultural aspect.